Wage differentials between declared and undeclared domestic workers - Suleman, F.; Figueiredo, M. C. T. (The Welfare State in Portugal in the Age of Austerity Conference, 2014)
Domestic workers contribute to national economies and enable other workers to carry out their own jobs. However, they lack recognition and working conditions, their wages are one of the lowest in the labour market, and are the most vulnerable category of workers. Furthermore, research has concentrated on structured and regular labour markets and notably leaves aside invisible and unskilled markets. Using original data, our paper attempts at filling this gap and offers empirical evidence of wage determination in the labour market of domestic workers in Portugal (N = 684). On average, domestic workers benefit from formal contracts. Compared to counterfactual group of undeclared workers, declaration of the employment relationship to social security authorities increases the hourly wage. In addition, the findings suggest that households demand for general and specific skills but are unwilling to reward them; and show that nationality affects significantly the earnings of the sampled domestic workers. Compared to the reference group of native workers, being African involves a wage penalty. There are also wage differentials associated to local labour market. This paper is connected with international discussion on domestic work and contributes to raise awareness on the role of regulations to promote decent work and reduce inequality.